REDUCE THE USE OF GADGETS: Parent’s coping strategies for children’s social development - Asirotul Marifah; Naning Puji Suryantini (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Today's technological advances are very rapid and increasingly sophisticated with the creation of gadgets. Gadgets greatly affect the development of elementary school students, especially developments in social interaction. The purpose of this study was to analyze the influence of the old usage of gadgets with the social development of school children. The design of this research is correlation analysis with the cross-sectional approach. The population in this study were all 1-5 grade students at Jabon 2 Mojoanyar Elementary School in Mojokerto Regency with 125 children. The sampling technique uses total sampling. The sample of this study amounted to 125 children. The research instrument used a social development questionnaire. Data analysis using crosstab. The results of this study indicate that most children use gadgets> 2 hours a day, 89 children (71.2%), and most school-age children have sufficient social development, 83 children (66.4%). The results of the crosstab analysis show that the longer children use gadgets, the less social development of children. Children who use gadgets over time from the time limit specified by some experts make them addicted and less sensitive to the surrounding environment. Children tend to be individual and passive in interacting with their social environment and peers. Keywords: Gadget, social Development, school-age children